Chemical Sterilization in MS Culture Medium for In vitro Culture of Philodendron sp. “Ruaysap” - Wamaedeesa, Raheema; Ali, Bakren; Chedao, Nusanisa; Kanjanawattanawong, Supanath (Princess of Naradhiwas University Journal, 2021)
This study aimed to investigate the appropriate chemicals and concentrations for disinfection of medium used to culture Philodendron “Ruaysap” shoot tip. The shoot tips were cultured on MS medium sterilized by adding Haiter® and Betadine® at 2, 4 and 6 mL/L for 60 days. The results showed both chemicals with all concentrations were able to inhibit the growth of microorganisms. Besides, it was found that the medium sterilized by adding 2 mL/L Haiter® increased foliar growth with the maximum number, length and width of leaves (6.3 leaves, 1.39 cm, 0.82 cm, respectively). Medium sterilized by adding 2, 4 and 6 mL/L Betadine® resulted in no difference in root number and length but the addition of Betadine® at all concentrations gave the number of roots greater than those sterilized by both autoclaving and adding Haiter®. After acclimatization for 30 days in greenhouse, all complete plantlets survived and grew well. Therefore, Haiter® and Betadine® are able to replace autoclaving which is a costly method.